1996
DOI: 10.1101/gad.10.19.2411
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of ATM leads to growth retardation, chromosomal fragmentation during meiosis, immune defects, and thymic lymphoma.

Abstract: ATM, the gene mutated in the inherited human disease ataxia-telangiectasia, is a member of a family of kinases involved in DNA metabolism and cell-cycle checkpoint control. To help clarify the physiological roles of the ATM protein, we disrupted the ATM gene in mice through homologous recombination. Initial evaluation of the ATM knockout animals indicates that inactivation of the mouse ATM gene recreates much of the phenotype of ataxia-telangiectasia. The homozygous mutant (ATM -/-) mice are viable, growth-ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
560
5
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 784 publications
(607 citation statements)
references
References 48 publications
(53 reference statements)
37
560
5
5
Order By: Relevance
“…Indeed, there is increasing evidence that growth failure in AT is caused directly by the impairment in ATM gene function. Growth failure is a prominent prenatal and postnatal feature of mutant atm -/-mice (23,24). Accordingly, human AT fibroblast lines, as well as fibroblasts from the atm -/-mice, grow slowly, undergo premature senescence, and have high requirements for growth factors (17,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, there is increasing evidence that growth failure in AT is caused directly by the impairment in ATM gene function. Growth failure is a prominent prenatal and postnatal feature of mutant atm -/-mice (23,24). Accordingly, human AT fibroblast lines, as well as fibroblasts from the atm -/-mice, grow slowly, undergo premature senescence, and have high requirements for growth factors (17,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Growth failure is a prominent prenatal and postnatal feature of mutant atm -/-mice (23,24). Accordingly, human AT fibroblast lines, as well as fibroblasts from the atm -/-mice, grow slowly, undergo premature senescence, and have high requirements for growth factors (17,(23)(24)(25). Impaired IGF-I activity may be implicated, as fibroblasts obtained from AT-affected individuals show low levels of IGF-I receptor (IGF-IR) expression and decreased IGF-IR promoter activity (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on AtmÀ/À MEFs have indicated a significant involvement of p53 and p21 in cellular defects dependent on the absence of ATM (Xu et al, 1996(Xu et al, , 1998. In fact, following DNA damage, ATM phosphorylates p53 and enhances its transcriptional activity on several target promoters, such as p21 (Lavin and Kozlov 2007).…”
Section: Hmga2 Interacts With and Is Phosphorylated By Atmmentioning
confidence: 97%
“…(Barlow et al,1996;Ch'ang et al, 2005;Peter et al, 2001) Immunodeficieny. (Elson et al,2001;Xu et al, 1996 ;Bagley et al, 2004) Osteoporosis. (Rasheed et al, 2006;Hishiya et al,2005) Shortened lifespan due to premature aging.…”
Section: Cell Intrinsicmentioning
confidence: 99%